A standardized gnotobiotic mouse model harboring a minimal 15-member mouse gut microbiota recapitulates SOPF/SPF phenotypes - Darnaud, Marion; De Vadder, Filipe; Bogeat, Pascaline; Boucinha, Lilia; Bulteau, Anne-Laure; Bunescu, Andrei; Couturier, Céline; Delgado, Ana; Dugua, Hélène; Elie, Céline; Mathieu, Alban; Novotná, Tereza; et al. (Nature communications, 2021)
Mus musculus is the classic mammalian model for biomedical research. Despite global efforts to standardize breeding and experimental procedures, the undefined composition and interindividual diversity of the microbiota of laboratory mice remains a limitation. In an attempt to standardize the gut microbiome in preclinical mouse studies, here we report the development of a simplified mouse microbiota composed of 15 strains from 7 of the 20 most prevalent bacterial families representative of the fecal microbiota of C57BL/6J Specific (and Opportunistic) Pathogen-Free (SPF/SOPF) animals and the derivation of a standardized gnotobiotic mouse model called GM15. GM15 recapitulates extensively the functionalities found in the C57BL/6J SOPF microbiota metagenome, and GM15 animals are phenotypically similar to SOPF or SPF animals in two different facilities. They are also less sensitive to the deleterious effects of post-weaning malnutrition. In this work, we show that the GM15 model provides increased reproducibility and robustness of preclinical studies by limiting the confounding effect of fluctuation in microbiota composition, and offers opportunities for research focused on how the microbiota shapes host physiology in health and disease.
Keywords: gnotobiologické modely; sekvenování celého genomu; organismy bez specifických patogenů; Feces; druhová specificita; fenotyp; Male; metagenomika; Phenotype; Specific Pathogen-Free Organisms; Metagenomics; Germ-Free Life; Bacteria; Gastrointestinal Microbiome; mužské pohlaví; Species Specificity; střevní mikroflóra; Body Weight; Animals; ženské pohlaví; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; Mice; Female; feces; tělesná hmotnost; Whole Genome Sequencing